Interpersonal Character of Sardunya in the Novel al-Bint Allatī Lā Tuḥibbu Ismahā by Elif Şafak - Uswatul Qodriyah (Journal of Arabic Literature (JaLi), 2026)
Personality development in children exposed to bullying is often described in general or moralistic terms, leaving the underlying interpersonal mechanisms unexamined. This study addresses that gap by using Harry Stack Sullivan's Interpersonal Theory of Psychiatry as an analytical lens to trace how the personality of Sardunya, the bullied main character in Elif Şafak's novel al-Bint Allātī Lā Tuḥibbu Ismāhā (The Girl Who Didn't Like Her Name), develops around a single stigmatized attribute: her name. Using a qualitative descriptive design, textual data were collected from the Arabic translation of the novel, coded deductively against Sullivan's four constructs — dynamism, personification, self-system, and cognitive process — and then purposively narrowed to the excerpts bearing directly on Sardunya's relationship to her name. The analysis shows that Sardunya's discomfort with her name predates the bullying itself, surfacing first as a quiet envy directed at the adults who named her; that repeated ridicule, especially during classroom roll call, fragments her self-image into Good Me, Bad Me, and Not Me, met chiefly by dissociation as a defense; and that her cognitive processing matures from parataxic impression to syntaxic judgment, a shift that eventually allows a single compliment about her name to register as trustworthy rather than as an exception. Read this way, Sardunya's development is not a wound that heals but an identity gradually reclaimed: by the novel's end, the mockery is not erased, but it no longer settles the question of who she is. The study offers literary scholars and educators a concrete account of how a stigmatized identity can be reworked through accumulated interpersonal experience rather than through any single corrective moment.